An Investigation Into the Concept of Brand Love and Its Proximal and Distal Covariates. Issue 3 (2nd July 2016) - Garg, Ruchi; Mukherjee, Jaydeep; Biswas, Soumendu; Kataria, Aarti
ABSTRACT: Brand love has emerged as an important marketing construct among practitioners and academics. Literature on brand love is mainly concentrated on its conceptualization rather than its antecedents and consequences. The authors have applied social exchange theory to the concept of brand love and proposed a conceptual model that highlights the factors affecting brand love, such as respect, brand's liking for consumers, and brand experience, as well as its behavioral outcomes, such as affective commitment, consumer citizenship behavior, and willingness to pay a price premium.